Cu2+ montmorillonite K10 clay catalyst as a green catalyst for production of stearic acid methyl ester: Optimization using response surface methodology (RSM) - Almadani E.A.; Harun F.W.; Radzi S.M.; Muhamad S.K. (Diponegoro University, 2024)
Clay catalyst has received much attention to replace the homogeneous catalysts in the esterification re-action to produce fatty acid methyl ester as the source of biodiesel as it is low cost, easily available, as well as environmental friendly. However, the use of unmodified clay, in particular montmorillonite K10 (MMT K10), for the esterification of fatty acids showed that the acid conversion was less than 60% and this is not preferable to the production of biodiesel. In this study, synthesis of stearic acid methyl ester using Cu2+-MMT K10 (Cu-MMT K10) was successfully optimized via response surface methodo-logy (RSM) based on 3-variable of Box-Behnken design (BB). The parameters were; reaction time (5-180 minutes), reaction temperature (80-120 C) and concentration of Cu2+ in MMT K10 (0.25-1 M). The use of RSM in optimizing the conversion of stearic acid was successfully developed as the actual experi-mental conversion of stearic acid was found similar to the actual values under the optimum conditions. The model equation predicted that the following conditions would generate the maximum conversion of stearic acid (87.05 % reaction time of 62 minutes, a reaction temperature of 80 'C and catalyst used is 1.0 M Cu-MMT K10. This finding can be considered as green catalytic process as it worked at moderate reaction temperature using low cost clay catalyst with a short reaction time.